Mexican American Parent's Perceptions of Culturally Congruent Interpersonal Processes of Care During Childhood Immunization Episodes: A Pilot Study - Teresa Keller (Rural Nurse Organization; Binghamton University, 2012)
One of the goals of Health People 2010 is to eliminate health disparities among minority populations by 2010, including improved childhood immunization rates among Mexican-American children. Prior research has identified the importance of interpersonal process-related factors as significant components of care sought by Mexican-Americans, but more knowledge is needed about what Mexican-American parents view as a beneficial relationship with the nurse during the immunization encounter. The purpose of this qualitative, descriptive pilot study was to explore and describe the perceptions of Mexican-American parents‟ regarding their relationships with clinic nurses in a rural, primarily agricultural community. Thematic analysis of data describes a beneficial relationship between Mexican American women, their children, and nurses during immunization encounters as consisting of 1) trust in the nurse, 2) building confidence in the mother and child, and 3) language concordance.